IMPLEMENTASI METODE USER-CENTERED DESIGN DALAM PENGEMBANGAN APLIKASI APP STORE BAGI UMKM - Nurmalasari; Siti Masturoh; Widi Astuti (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2026)
Small, Medium, and Micro Enterprises (SMMEs) play a crucial role in driving economic growth. Even so, the adoption of digital technology among SMMEs is still quite low, especially in communities with limited digital literacy. This study aims to implement the User-Centered Design (UCD) method in developing an SMME App Store application for the Upgraded SMME Community in Bekasi City. The initial interview results showed that the community has more than 50 MSME members, but only about 20% have used a digital platform to support their business activities. To tackle this issue, a mobile app was developed to help manage business profiles, promote products, categorize products, interact with customers, and handle orders through WhatsApp integration. This research applied the User-Centered Design (UCD) methodology based on ISO 9241-210 standards, which consists of five stages: plan the human-centered design process, specify the context of use, specify user and organizational requirements, produce design solutions, and evaluate design user requirements. Data was collected through observation, interviews, and literature studies as a basis for designing the application. Based on functional testing results using Black Box Testing, usability evaluation using SUS with a score of 81.25, and limited implementation with 30 members of the UMKM Naik Kelas Community in Bekasi City, the developed application has met functional needs and has a good level of ease of use, thus supporting the promotion and marketing of UMKM products.